Neuroprotective Effects of Diabetes Drugs for the Treatment of Neonatal Hypoxia-Ischemia Encephalopathy - Poupon-Bejuit, Laura; Rocha-Ferreira, Eridan; Thornton, Claire; Hagberg, Henrik; Rahim, Ahad A. (Frontiers in Cellular Neuroscience, 2020)
The perinatal period represents a time of great vulnerability for the developing brain. A variety of injuries can result in death or devastating injury causing profound neurocognitive deficits. Hypoxic-ischemic neonatal encephalopathy (HIE) remains the leading cause of brain injury in term infants during the perinatal period with limited options available to aid in recovery. It can result in long-term devastating consequences with neurologic complications varying from mild behavioural deficits to severe seizure, intellectual disability, and/or cerebral palsy in the newborn. Despite medical advances, the only viable option is therapeutic hypothermia which is classified as the gold standard but is not used, or may not be as effective in preterm cases, infection-associated cases or low resource settings. Therefore, alternatives or adjunct therapies are urgently needed. Ongoing research continues to advance our understanding of the mechanisms contributing to perinatal brain injury and identify new targets and treatments. Drugs used for the treatment of patients with type 2 diabetes (T2DM) have demonstrated neuroprotective properties and therapeutic efficacy from neurological sequelae following HIE insults in preclinical models, both alone, or in combination with induced hypothermia. In this short review, we have focused on recent findings on the use of diabetes drugs that provide a neuroprotective effect using in vitro and in vivo models of HIE that could be considered for clinical translation as a promising treatment.